EXPERIENCES OF HOME CARE STAFF WITH THE STAY ACTIVE AT HOME PROGRAM. (11th November 2018) - Metzelthin, S F; Smeets, R G M; Hanssen, W A G; Zijlstra, G A R; van Rossum, E; de Man-van Ginkel, J M; Kempen, G I J M
Abstract: Reablement aims to empower people to age in place with the highest degree of self-reliance. However, this requires a behavioral change in home care staff who tend to do things for instead of with their clients. Therefore the "Stay Active at Home" program was developed. To explore the experiences of home care staff with the program 21 semi-structured interviews with home care professionals were conducted. The results showed that the program was perceived as a valuable strategy to implement the principals of Reablement in practice. Self-efficacy raising activities, like peer discussions and role plays, were considered as important components of the program. Nevertheless, some participants indicated to struggle with implementing Reablement in challenging situations, e.g. when clients show resistance. Participants suggested several program improvements. Furthermore, they expressed a need for more structural and explicit support from colleagues and management. These experiences were used to further improve the program.